2022
DOI: 10.1021/acschemneuro.2c00144
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Activity of a Novel Synthetic Rhodamine-Based Hydrazone against Cu2+-Induced Alzheimer’s Disease in Drosophila

Abstract: A new rhodamine-based probe 3,5-di-tert-butylsalicylaldehyde rhodamine hydrazone (RHTB) has been synthesized and well characterized using spectroscopic techniques and single-crystal X-ray crystallography. Among several metal ions, it selectively detects Cu2+ ions as monitored by UV–Vis and emission spectral titrations. It displays “turn on” behavior owing to the opening of a spirolactum ring and the presence of 3,5-di-tert-butyl as an electron releasing group. Further, Cu2+ ions play a pivotal role in extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Subsequently, we have established a model system of transgenic AD Drosophila using ey-GAL4/CyO driver strains for misexpressing Aβ 42 protein in the eye imaginal disc of the 3rd instar larvae [ 39 ]. The transgenic flies exhibited neurodegenerated phenotype in their eye imaginal disc.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we have established a model system of transgenic AD Drosophila using ey-GAL4/CyO driver strains for misexpressing Aβ 42 protein in the eye imaginal disc of the 3rd instar larvae [ 39 ]. The transgenic flies exhibited neurodegenerated phenotype in their eye imaginal disc.…”
Section: Resultsmentioning
confidence: 99%
“…22 The LOD was 3.07 Â 10 À7 M. Another group used EtOH : HEPES buffer (1 : 1, v/v) as the medium where the cation induced opening of the spirolactam ring followed by coordination with amide O and imine N. 23 They reported the LOD value to be 1.16 Â 10 À6 M. Chauhan and co-workers performed their experiments in acetonitrile : H 2 O (7 : 3, v/v, pH 7.4) for the detection of the cation. 24 They also proposed opening of the spirolactam ring followed by a coordination mechanism but they reported coordination of Cu with amide O, imine N and phenolic O atoms (Fig. 1).…”
Section: Salicylaldehyde-incorporated Chemosensorsmentioning
confidence: 99%
“…Subsequently, Srikrishna et al. also designed and synthesized a rhodamine‐based hydrazine 59 (Figure 9) for Cu 2+ capture and AD treatment [108] . Probe 59 could coordinate with Cu 2+ by the O−N−O atoms in a 1 : 1 stoichiometric ratio.…”
Section: Small Molecular Fluorescent Probes For Ad Associated Active ...mentioning
confidence: 99%
“…Subsequently, Srikrishna et al also designed and synthesized a rhodamine-based hydrazine 59 (Figure 9) for Cu 2 + capture and AD treatment. [108] Probe 59 could coordinate with Cu 2 + by the OÀ NÀ O atoms in a 1 : 1 stoichiometric ratio. With probe 59, the authors revealed the therapeutic potential of 59 against Cu 2 + -induced Aβ 42 toxicity in AD model of Drosophila.…”
Section: Metal Ionsmentioning
confidence: 99%